Measuring the empathy levels among pharmacy students: a journey toward enhancing effective communication and understanding in the pharmacist-patient relationship - Ahmad, Alhareth; Nassar, Razan I.; Thiab, Samar; Alostath, Mohammad; Aldarawish, Rania; Ramahi, Sofiyan Mohd; Abed, Anas; Assiri, Ahmad A. (Frontiers in Communication, 2024)
BackgroundEmpathy is an essential skill for healthcare professionals, including pharmacists, because it improves person-centered care and treatment outcomes. Measuring the level of empathy among pharmacy students gives an understanding and insight into their readiness for incorporating a person-centered practice in their future work. This study aimed to assess empathy levels among Jordanian pharmacy students and explore the factors influencing these levels.MethodsA cross-sectional study using a web-based survey was conducted among currently enrolled pharmacy students from various academic years at both public and private Jordanian universities. The survey consisted of three sections; demographics, the Interpersonal Reactivity Index (IRI) to identify pharmacy students’ empathy level, and items specifically related to the pharmacist-patient relationship. Statistical analysis was conducted using SPSS software. Multiple linear regression was used to reveal the factors affecting students’ empathy.ResultsA total of 396 pharmacy students participated in the current study, with a mean age of 21.65 years (SD = 2.865), and about three-quarters were female (73.5%). The mean IRI score for the students was 70.89 (SD = 12.82), with subscale means as follows: perspective-taking (18.52), fantasy (17.05), empathic concern (20.16), and personal distress (15.16). Students’ age, gender, awareness of the term empathy, and studying empathy at universities were among the factors that significantly affected the students’ empathy scores.ConclusionThe present study reveals moderate empathy levels among Jordanian pharmacy students and sheds light on an understudied aspect within the pharmacy practice in Jordan. Significant demographic and educational factors affected the pharmacy students’ empathy levels. Incorporating empathy education in pharmacy curricula can better prepare pharmacy students for person-centered care.